Study on Association of Serum Ferritin With Thyroid Profile And Oral Glucose Tolerance Test in Thalassemia Major Children - Khan, Kalimuddin; Saha, Sudip; Pal, Partha Pratim; Bera, Aparajita; Birua, Shyama (Journal of Nepal Paediatric Society, 2020)
Introduction: The free iron and haemosiderosis-induced damage of the endocrine glands cause endocrinopathies such as abnormal glucose tolerance and hypothyroidism in transfusion - dependent beta-thalassemia major patients. Our objective was to study the association of serum ferritin level with thyroid dysfunctions; abnormal blood glucose tolerance and to see if they appear in the earlier period of life. Methods: This cross-sectional study was done among thalassemia major children of two to 12 years in a tertiary care hospital, Kolkata, India. A pre-designed proforma was filled. Serum ferritin, fT4, TSH level, and oral glucose tolerance test (OGTT) were measured at presentation and noted in proforma. Results: A total of 80 thalassemic children were studied. Fiftieth percentile cut off value (1414 ng/ml) of serum ferritin was found to be significant with associated variables like normal fT4, TSH, and OGTT. Out of all study subjects, 39 (51.3%) of normal fT4, 39 (54.9%) of normal TSH and 39 (52.0%) of normal OGTT had ferritin < 50th percentile (P < 0.05). Nine (11.3%) children had abnormal thyroid profiles and five (6.3%) children had abnormal OGTT having ferritin > 2000 ng/ml. At a cut off value of ferritin level > 1414 ng/ml, fT4, TSH and OGTT showed significant abnormality (p < 0.05 with df 1). Conclusions: Ferritin is a good indirect marker to assess the risk of endocrine abnormality in thalassemic children. Frequent monitoring should be done once ferritin level crosses 1000 ng/ml. This will help in early detection and timely management of thalassemia related endocrinopathies.